'Good Governance', Daya Saing dan Investasi Global - Zaenal Soedjais (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
The on going process of globalization leaves no room for Indonesian access to global investment unless the country manage to ensure the competitivess its system. Improving institutional capacity to be able of delivering good governance and good corporate governenve are inevitable. The challenge is how to allow the market to perform optimally.